\[ V(h) = \begin{cases} -2h-3 & \text { on } [-6, -2] \\ -(h+3)(h-3) & \text { on } (-2, 4] \\ \frac {7h}{4} - 8 & \text { on } (4,8) \end{cases} \]
\[ K(m) = \begin{cases} m+4 & \text { on } (-7, 0] \\ m^2-7m+9 & \text { on } (1,6] \end{cases} \]
Calculate the following expressions using the definitions above. Type DNE for ”does not exist”.
\[ \begin{array}{rrl|rrl} (1) & V(-2) & = \answer {1} & (2) & K(0) & =\answer {4} \\ (3) & V(4) & = \answer {-7} & (4) & K(2) & =\answer {-1} \\ (5) & V(6-2) & = \answer {-7} & (6) & 3-K(3) & =\answer {6} \\ (7) & (V(1))^2 & = \answer {64} & (8) & K(-6)K(0) & =\answer {-8} \\ & & & & & \\ (9) & V(-4) & = \answer {5} & (10) & K(V(-4)) & =\answer {-1} \\ (11) & V(-3) & = \answer {3} & (12) & K(V(-3)) & =\answer {-3} \\ (13) & V(5) & = \answer {\frac {3}{4}} & (14) & K(V(5)) & =\answer {DNE} \\ (15) & K(-3) & = \answer {1} & (16) & V(K(-3)) & =\answer {8} \\ & & & & & \\ (17) & V(-5) & = \answer {7} & (18) & V(V(-5)) & =\answer {\frac {17}{4}} \\ (19) & V(-2) & = \answer {1} & (20) & V(V(-2)) & =\answer {8} \\ (21) & K(0) & = \answer {4} & (22) & K(K(0)) & =\answer {-3} \\ (23) & K(-4) & = \answer {0} & (24) & K(K(-4)) & =\answer {4} \end{array} \]